Advance directive for health care. evolution and current status - Pezzano, Laura C. (Revista del Hospital Italiano de Buenos Aires, 2013)
Modern medicine has placed in the hands of healthcare services a set of practices that professionals must manage with criteria that, although are purely medical in theory, have a discretionary component due to which it is very important for the doctor to know the ways of thinking and appreciating the life of their patients. In the context of Advanced Care Planning, advanced directives constitute useful tools in preserving the autonomy of patients at the end of life and, although their value has been recognized for over 30 years, their use has still presented an uneven acceptance. This article provides an overview of their history and discusses some recent aspects of their legislation